KONTRIBUSI PONDOK PESANTREN NGALAH DALAM MEMBENTUK KARAKTER SANTRI DI ASRAMA I - Juliatin Juliatin; Ali Mukhtarom; Achmad Marzuki; Achmat Mubarok (Tasyri’: Jurnal Tarbiyah – Syari’ah Islamiyah, 2025)
The Ngalah Islamic Boarding School is a Islamic boarding school located in the Sengon Agung area, Purwosari Pasuruan, which has a mixed feel of classic and modern, classic because there are still many yellow books that are studied in this Islamic boarding school while preserving the characteristics of Islamic boarding schools, namely rote memorization and modern recitation because apart from studying the books here are modern because the Islamic boarding school also provides formal education starting from the MI level to the university level which is named Yudharta Pasuruan University which is still in demand by many groups as evidenced by the large number of data on new students who have just studied here. the focus of this research is to find out how to shape the character of the santri through various activities, both religious and social, for example in the religious field: such as performing congregational prayers at any time except during midday, students are not required to pray in congregation because they are constrained by lectures that usually occurs during the day. Recitation of various yellow books, both discussing muamalah (social) and worship, muamalah such as the book of maroqil ubudiah, books that discuss marriage that have been studied in hostel I include: fathul inzar, book of marriage, qurrotul uyun, book of nihayatus zain and other books